Multi-Energy Flow Calculation Considering the Convexification Network Constraints for the Integrated Energy System - Chen, Danlei; Bai, Xiaoqing (Frontiers in Energy Research, 2021)
To alleviate environmental pollution and improve the energy efficiency of end-user utilization, the integrated energy systems (IESs) have become an important direction of energy structure adjustment over the world. The widespread application of the coupling units, such as gas-fired generators, gas-fired boilers, and combined heat and power (CHP), increases the connection among electrical, natural gas, and heating systems in IESs. This study proposes a mixed-integer nonlinear programming (MINLP) model combining electrical, natural gas, and heating systems, as well as the coupling components, such as CHP and gas-fired generators. The proposed model is applicable for either the radial multi-energy network or the meshed multi-energy network. Since the proposed MINLP model is difficult to be solved, the second-order cone and linearized techniques are used to transform the non-convex fundamental matrix formulation of multi-energy network equations to a mixed-integer convex multi-energy flow model, which can improve the computational efficiency significantly. Moreover, the potential convergence problem of the original model can also be avoided. A simulation of IEEE 14-node electrical system, 6-node natural gas system, and 23-node heating system are studied to verify the accuracy and computational rapidity of the proposed method.